Reconstruction of Soft Tissue Defects of Upper Extremity - Fatima, Moeez; Khan, Faisal Akhlaq Ali (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: This study aims to evaluate the etiology of upper extremity soft tissue defects and determine the outcome of the various methods for covering upper limb soft tissue defects. METHODOLOGY: This case series study was done at the Plastic and reconstructive Surgery department Civil Hospital, Karachi, from December 2018 to May 2019. Seventy-six cases were operated on in the department of plastic surgery. All patients with upper extremity defects with or without exposed bone, open fractures, and early presentation were included. Segmental bone defects, dirty wounds and patient’s denial of consent were excluded. The mechanism of injury, association with fractures and the method of fixation was documented. Radiographic images were taken. Further, the functional and aesthetic outcome was assessed. Performa data has been analyzed using SPSS 21. RESULTS: The mean age of the patient was 33±10.87 years. Road traffic accidents 32.89% and machine cut injuries 31.58% were the commonest etiologies of upper limb defects. Postburn contracture was seen in 10.53%, secondary to debridement at 13.16%, secondary to fasciotomy at 3.95%, secondary to flap harvest at 6.58%, and secondary to tumor resection at 1.32%. 33(43.42%) upper limb defects were treated by grafting, and flaps were used in 43(56.58%). CONCLUSION: Road traffic accidents and machine cut injuries are the main etiological factors of upper extremity defects. Grafting and flaps are used in the management of soft tissue defects. They have relatively low complication rates, provided that all measures should be taken to eliminate soft tissue or bone infection. KEYWORDS: Soft tissue defect, Upper extremity defects, soft tissue coverage, Flaps for upper limb, Upper extremity reconstruction, Upper limb trauma.